Visible Light Communication and Leaky Feeder for 5g and 6g - Canete-Arratia, L; Adasme-Soto, P; Viveros-Llabres, A (Institute of Electrical and Electronics Engineers Inc., 2024)
This work presents Visible Light Communication (VLC) and Leaky Feeder technologies, explaining their channel models and how they can contribute to current wireless communications. Their main standards are described, and a brief comparison is made between them, highlighting that they can be used either as alternatives or in a complementary way in enclosed spaces, like tunnels, where Wi-Fi may not be efficient. Although these technologies are not new, their implementation is still developing, especially VLC, which has recently gained significant momentum. Finally, due to their characteristics, both VLC and Leaky Feeder can make a valuable contribution to 5G networks and the future development of 6G. © 2024 IEEE.